Optimum O2:CH4 Ratio Promotes the Synergy between Aerobic Methanotrophs and Denitrifiers to Enhance Nitrogen Removal - Zhu, Jing; Xu, Xingkun; Yuan, Mengdong; Wu, Hanghang; Ma, Zhuang; Wu, Weixiang (Frontiers in Microbiology, 2017)
The O2:CH4 ratio significantly effects nitrogen removal in mixed cultures where aerobic methane oxidation is coupled with denitrification (AME-D). The goal of this study was to investigate nitrogen removal of the AME-D process at four different O2:CH4 ratios (0, 0.05, 0.25 and 1 (v/v)). In batch tests, the highest denitrifying activity was observed when the O2:CH4 ratio was 0.25. At this ratio, the methanotrophs produced sufficient carbon sources for denitrifiers and the oxygen level did not inhibit nitrite removal. The results indicated that the synergy between methanotrophs and denitrifiers was significantly improved, thereby achieving a greater capacity of nitrogen removal. Based on thermodynamic and chemical analyses, methanol, butyrate and formaldehyde could be the main trophic links of AME-D process in our study. Our research provide valuable information for improving the practical application of the AME-D systems.